Impact of Sex: Determination of Alcohol Neuroadaptation and Reinforcement - Finn, A Deborah; Wiren, Kristine M; Hashimoto, Joel G.; Alele, Paul E; Devaud, Leslie L.; Price, Kimber L.; Middaugh, Lawrence D. (ALCHOLISM,Clinical and experimental Research, 2006)
his article represents the proceedings of a symposium at the Research Society on Alcoholism meeting in Santa Barbara, California. The organizers/chairs were Kristine M. Wiren and Deborah A. Finn. Following a brief introduction by Deborah Finn, the presentations were (1) The Importance of Gender in Determining Expression Differences in Mouse Lines Selected for Chronic Ethanol Withdrawal Severity, by Kristine M. Wiren and Joel G. Hashimoto; (2) Sex Differences in Ethanol Withdrawal Involve GABAergic and Stress Systems, by Paul E. Alele and Leslie L. Devaud; (3) The Influence of Sex on Ethanol Consumption and Reward in C57BL/6 Mice, by Kimber L. Price and Lawrence D. Middaugh; and (4) Sex Differences in Alcohol Self‐administration in Cynomolgus Monkeys, by Kathleen A. Grant.
Keywords: Ethanol Withdrawal; Ethanol Self‐administration; Microarrays; Gene Expression; Mesolimbic Dopamine System; Prefrontal Cortex; Ventral Tegmental Area